2019
DOI: 10.1172/jci.insight.123490
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte glycolysis determines CD8+ T cell functionality in human Chagas disease

Abstract: dinucleotide (NADH) and flavin adenine dinucleotide, which donate electrons to the electron transport chain to fuel oxidative phosphorylation (OXPHOS), the process by which 32 ATP molecules are generated in the mitochondria.In inflammatory settings, OXPHOS is inhibited by nitric oxide (NO) production in monocyte-derived inflammatory dendritic cells (moDCs) in an autocrine manner. In the absence of an active respiratory chain, sustained glycolytic metabolism is essential for moDC survival and function (9). Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…membrane is a platform for the NLRP3 inflammasome [266]. There exist several known signal transduction pathways between the cell and its mitochondria [267] The glycolytic pathway is vital for monocyte function and monocyte-derived cells' differentiation and functions (see Table 8): (i) the glycolytic pathway influences monocyte differentiation into macrophages and dendritic cells [261,[276][277][278]; (ii) glycolysis is upregulated in monocytes in response to infection and is important for effector functions [279][280][281], and the Akt-mTOR-HIF-1-α pathway seems especially important [268,[276][277][278]; (iii) trained monocytes are mainly glycolytic [94,245,282].…”
Section: Mmp9mentioning
confidence: 99%
See 1 more Smart Citation
“…membrane is a platform for the NLRP3 inflammasome [266]. There exist several known signal transduction pathways between the cell and its mitochondria [267] The glycolytic pathway is vital for monocyte function and monocyte-derived cells' differentiation and functions (see Table 8): (i) the glycolytic pathway influences monocyte differentiation into macrophages and dendritic cells [261,[276][277][278]; (ii) glycolysis is upregulated in monocytes in response to infection and is important for effector functions [279][280][281], and the Akt-mTOR-HIF-1-α pathway seems especially important [268,[276][277][278]; (iii) trained monocytes are mainly glycolytic [94,245,282].…”
Section: Mmp9mentioning
confidence: 99%
“…Ctype lectin signalling seems to trigger glycolysis when challenged by pathogens, and both glycolysis and the pentose phosphate pathway are then required for ROS production/ [279] Monocytes in Chagas patients are mainly glycolytic, and monocyte glycolysis determines CD8+ T-cell functionality . [280] CD14 + monocytes from rheumatoid arthritis patients express IL-1β, TNFα, IL-6, IL-27, CXCL10, and CXCL11, and are highly glycolytic, with increased expression of HIF1α, HK, and PFKFB3, which is mediated by STAT3. [281] Amino acid transporter SLC7A5 and mediated amino acid uptake in monocytes influence cytokine production, and inhibition of SLC7A5 is associated with the downregulation of glycolysis during LPS activation.…”
Section: Description Of Findingsmentioning
confidence: 99%
“…For ATP production, monocytes rely both on oxidative phosphorylation (OXPHOS) and glycolysis (Kramer et al , 2014). However, under conditions that diverge from normal physiology, including inflammation or hypoxia, monocytes activate transcriptional responses that modulate or change cellular metabolism and induce a preferential use of one of the two pathways (Sanmarco et al , 2019). Recent studies have shown that monocyte bioenergetics and inflammatory phenotype can change in response to different infections or pathological stimuli such as hypoxia (Yamada et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, circulating T-lymphocytes display reduced expression of CD39 and CD73 ecto-enzymes in T. cruzi-chronically infected asymptomatic patients, 65 which also exhibit increased plasmatic ATP levels in comparison with control noninfected donors. 66 and diminish local parasite burden. 33 Considering the limited regenerative capacity of cardiomyocytes, CD73-derived adenosine could be a critical metabolite to protect the heart from excessive inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…76 inflammatory environment. 66 Interestingly, HIF-1 also drives the expression of adenosine A2B receptor (ADORA2B) by direct binding to the receptor promoter. 77 During a chronic infection, low levels of adenosine chronically signaling through ADORA2A may contribute to immunosuppression, thereby increasing the impact of infection.…”
Section: Discussionmentioning
confidence: 99%